Pendampingan Sekolah Daring Siswi Kelas VII Mts Taufiqiyyatul Asna Bukaan Saat Pandemi Covid-1¬9 di Pondok Pesantren Putri Ishlahiyyatul Asroriyyah - Badiatun Ni’mah; Fadhil Akbar (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2021)
School is a place where a child can get an education, add knowledge, a place to find identity, hone skills and much more. Therefore, even though during the COVID-19 pandemic like today the government still strives for a learning that can still be carried out even though it must be online, all this is done because an education is very important, especially for children. Which is expected that children will still get an education even though it is not optimal, of course this is because it is still where the adjustment period from offline to online, therefore researchers take the initiative to assist online schools during the current pandemic, which is expected to be able to help adjust children in undergoing online learning. In this study, the authors used the PAR (Participatory Action Research) method. The PAR method is a research model that seeks something to connect a research process in a process of social change. By directly participating in assisting Mts students in carrying out online schools with television media, it is hoped that they can maximize the implementation of online schools in terms of conditioning.